2014
DOI: 10.1186/1471-2296-15-19
|View full text |Cite
|
Sign up to set email alerts
|

The development of a guideline implementability tool (GUIDE-IT): a qualitative study of family physician perspectives

Abstract: BackgroundThe potential of clinical practice guidelines has not been realized due to inconsistent adoption in clinical practice. Optimising intrinsic characteristics of guidelines (e.g., its wording and format) that are associated with uptake (as perceived by their end users) may have potential. Using findings from a realist review on guideline uptake and consultation with experts in guideline development, we designed a conceptual version of a future tool called Guideline Implementability Tool (GUIDE-IT). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The interviewer asked participants to reflect on any factors that would facilitate or prohibit them from using the tool. Items derived from the GUIDE-IT tool framed questions of the initial interview guide that addressed the tool's implementability [35]. Participants were also asked about how they think the tool should be introduced to clinicians and how to have it available at their practice sites.…”
Section: Interview Methods and Research Instrumentmentioning
confidence: 99%
“…The interviewer asked participants to reflect on any factors that would facilitate or prohibit them from using the tool. Items derived from the GUIDE-IT tool framed questions of the initial interview guide that addressed the tool's implementability [35]. Participants were also asked about how they think the tool should be introduced to clinicians and how to have it available at their practice sites.…”
Section: Interview Methods and Research Instrumentmentioning
confidence: 99%
“…In focus groups and interviews with 62 medical directors about how to increase use of the American College of Occupational and Environmental Medicine’s guidelines, the need for quick reference tools was a high priority [30]. In interviews and focus groups with 20 family physicians about their preferences for guideline content and format, participants expressed the need for guideline summaries including charts, tables and algorithms [31]. Interviews with 28 health professionals from four intensive care units revealed that GItools such as checklists which could be quickly consulted as a reminder were viewed as enablers of guideline implementation [32].…”
Section: Discussionmentioning
confidence: 99%
“…10 In particular, primary care physicians perceive barriers and facilitators to guideline uptake almost exclusively according to their format, language and usability. 11 Accordingly, the style in which a guideline is written (e.g., providing suggested actions rather than prohibitive rules) influences how it is received and whether it will be followed. 12 In an observational study involving general practitioners in the Netherlands, vague and imprecisely defined recommendations were followed in 36% of clinical decisions, whereas clear recommendations were followed in 67% of decisions.…”
Section: Why Don't Clinicians Use Guidelines?mentioning
confidence: 99%
“…Ideally, end-users of a guideline should also be involved in this process. Recent work suggests that primary care physicians can be successfully engaged in objectively assessing language and format attributes of recommendations and improving these according to their preferences 11 (a worksheet from this process is included in Appendix 5, available at www.cmaj.ca/lookup/ suppl/doi: 10.1503/cmaj.151102/-/DC1). Efforts could be initiated by individual guideline committees.…”
mentioning
confidence: 99%